Apoptosis - Rudner, Justine (IntechOpen, 2013)
The book "Apoptosis", published by InTech and edited by Dr. Justine Rudner, of the Department of Radiation Oncology, University Hospital of Tuebingen, Germany, is comprised of 8 Open Access chapters, covering a wide range of Apoptosis-related scientific research.